Price, wage and employment response to shocks: evidence from the WDN survey - Giuseppe Bertola; Aurelijus Dabušinskas; Marco Hoeberichts; Mario Izquierdo; Claudia Kwapil (Deutsche Bundesbank, 2010)
This paper analyses information from survey data collected in the framework of the Eurosystem's Wage Dynamics Network (WDN) on patterns of firm-level adjustment to shocks. We document that the relative intensity and the character of price vs. cost and wage vs. employment adjustments in response to cost-push shocks depend - in theoretically sensible ways - on the intensity of competition in firms' product markets, on the importance of collective wage bargaining and on other structural and institutional features of firms and of their environment. Focusing on the passthrough of cost shocks to prices, our results suggest that the pass-through is lower in highly competitive firms. Furthermore, a high degree of employment protection and collective wage agreements tend to make this pass-through stronger.
Keywords: J31; J38; P50; 330; Wage bargaining; labour-market institutions; survey data; European Union; Preis; Kosten; Schock; Arbeitskosten; Betriebliche Preispolitik; Wettbewerb; Tarifpolitik; Arbeitsmarktflexibilisierung; Arbeitnehmerschutz; EU-Staaten